1917
DOI: 10.1042/bj0110079
|View full text |Cite
|
Sign up to set email alerts
|

On the Oxidation of Amino-acids and of related substances with chloramine-T

Abstract: Reference has already been made [1916, 1, 2] to the oxidation of certain amino-acids with hypochlorite and with chloramine-T. The latter term is the abbreviated name for sodio-p-toluenesulphochloroamine, a substance which appears to constitute a useful addition to the small-class of neutral oxidising agents. These experiments seemed worth extending, partly because interesting products of oxidation were likely to be met with and also as preliminary to a study of the mode of antiseptic action of substances of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

1942
1942
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(23 citation statements)
references
References 0 publications
0
23
0
Order By: Relevance
“…Formation of an aldehyde from an ␣-amino acid by HOCl was first reported at the beginning of the last century (60,61). Recent reinvestigation of the issue showed that formation of a chloramine at the ␣-amino group is the first reaction step (24).…”
Section: Discussionmentioning
confidence: 99%
“…Formation of an aldehyde from an ␣-amino acid by HOCl was first reported at the beginning of the last century (60,61). Recent reinvestigation of the issue showed that formation of a chloramine at the ␣-amino group is the first reaction step (24).…”
Section: Discussionmentioning
confidence: 99%
“…If a stoichiometric reaction is to take place between chloramine-r and the substance titrated, no further reaction is allowable. It is surprising that there are no reports of any recent investigation to determine whether there is any further reaction between these two cornpounds, for H. D. Dakin reported, 51 in 1917, that benzaldehyde p-sulfonamide is formed when they are heated together in aqueous solution.…”
Section: -Ethylanthraquinonementioning
confidence: 92%
“…Gas chromatography analysis was performed with a Hewlett-Packard HP 5980 gas chromatograph Compound 1 (14.5 mg, 0.03 mmol) was dissolved by sonication in neutral 1 % aqueous solution of chloramine-T (N-chloro-p-toluenesulfonamide sodium salt; 10.26 mg, 0.045 mmol), and the reaction was allowed to run for 10 min. [47] Excess alkali was neutralized with acetic acid. The reaction products were oxidized by Jones reagent under synchronous stirring for 10 min at 50°C.…”
Section: Methodsmentioning
confidence: 99%